Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.1136/rmdopen-2022-002511
|View full text |Cite
|
Sign up to set email alerts
|

Anti-RA33 antibodies are present in a subset of patients with immune checkpoint inhibitor-induced inflammatory arthritis

Abstract: ObjectivePatients with inflammatory arthritis (IA) associated with immune checkpoint inhibitor (ICI) treatment for cancer are typically seronegative for anti-cyclic citrullinated peptide (CCP) antibodies and rheumatoid factor, but little is known about the presence of other autoantibodies in this patient population. We investigated the prevalence and characteristics of anti-RA33 antibodies in patients with ICI-induced IA.MethodsAnti-RA33 ELISAs were performed on sera from four groups of patients: 79 with ICI-i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 25 publications
0
5
0
1
Order By: Relevance
“…2023;61(3):276-291 энтезита, энтезопатии, аксиального воспаления и псориатического поражения кожи, характерных для СпА [180][181][182][183][184]. В сыворотках пациентов были обнаружены анти-РA33 [185], которые, как уже отмечалось, выявляются у пациентов с серонегативным РА [89]. Являются ли анти-PA33 биомаркером особого субтипа серонегативного РА, патогенетически связанного с ингибицией CTLA-4 (cytotoxic T-lymphocyte-associated protein 4), в настоящее время не известно.…”
Section: Discussionunclassified
“…2023;61(3):276-291 энтезита, энтезопатии, аксиального воспаления и псориатического поражения кожи, характерных для СпА [180][181][182][183][184]. В сыворотках пациентов были обнаружены анти-РA33 [185], которые, как уже отмечалось, выявляются у пациентов с серонегативным РА [89]. Являются ли анти-PA33 биомаркером особого субтипа серонегативного РА, патогенетически связанного с ингибицией CTLA-4 (cytotoxic T-lymphocyte-associated protein 4), в настоящее время не известно.…”
Section: Discussionunclassified
“…It is interesting to mention that signs of B cell activation and antibody production have also been recently described in the classical seronegative arthitides arising in course of ICIs. Cappelli et al (40) showed that more than 11% of patients with seronegative ICI-induced arthritis had anti-RA33 antibodies, whereas none of the patients not developing arthritis had these antibodies. Similarly, a significant increase in transitional B cells and specific autoantibodies to joint-related proteins was documented in a prospective cohort of patients treated with ICI for melanoma who developed inflammatory arthritis (41).…”
Section: Novel Antibodiesmentioning
confidence: 99%
“…In contrast, according to a study by Cappelli, anti-RA33 antibodies were detected in 11.4% of patients with ICI-induced arthritis, whereas none of the ICI-treated controls without arthritis tested positive [ 88 ]. The antibodies were also present in 7.7% of patients with RA and 2% of healthy controls, suggesting that autoantibodies may play a role in ICI-induced arthritis or that individuals with pre-existing autoantibodies are at risk of ICI-induced arthritis.…”
Section: Rheumatic Iraesmentioning
confidence: 99%